The influence of genetic ancestry and ethnicity on breast cancer survival associated with genetic variation in the TGF-β-signaling pathway: The Breast Cancer Health Disparities Study - Slattery, Martha L. (2013)
The TGF-β signaling pathway regulates cellular proliferation and differentiation. We evaluated genetic variation in this pathway, its association with breast cancer survival, and survival differences by genetic ancestry and self-reported ethnicity. The Breast Cancer Health Disparities Study includes participants from the 4-Corners Breast Cancer Study (n = 1391 cases) and the San Francisco Bay Area Breast Cancer Study (n=946 cases) who have been followed for survival. We evaluated 28 genes in the TGF-β signaling pathway using a tagSNP approach. Adaptive rank truncated product (ARTP) was used to test the gene and pathway significance by Native American (NA) ancestry and by self-reported ethnicity (non-Hispanic white (NHW) and Hispanic/NA). Genetic variation in the TGF-β signaling pathway was associated with overall breast cancer survival (P(ARTP) = 0.05), especially for women with low NA ancestry (P(ARTP) =0.007) and NHW women (P(ARTP) =0.006). BMP2, BMP4, RUNX1. and TGFBR3 were significantly associated with breast cancer survival overall (P(ARTP)=0.04, 0.02, 0.002, and 0.04 respectively). Among women with low NA ancestry associations were: BMP4 (P(ARTP) = 0.007), BMP6 (P(ARTP) = 0.001), GDF10 (P(ARTP)=0.05), RUNX1 (P(ARTP)=0.002), SMAD1 (P(ARTP)=0.05), and TGFBR2 (P(ARTP)=0.02). A polygenic risk model showed that women with low NA ancestry and high numbers of at-risk alleles had twice the risk of dying from breast cancer as did women with high NA ancestry. Our data suggest that genetic variation in the TGF-β signaling pathway influences breast cancer survival. Associations were similar when the analyses were stratified by genetic ancestry or by self-reported ethnicity.